Cerebral blood flow regulation is not acutely altered after a typical number of headers in women footballers - Jack, Jacob; Woodgates, Alex; Smail, Oliver; Brown, Felix; Lynam, Katie; Lester, Alice; Williams, Genevieve; Bond, Bert (Frontiers in Neurology, 2022)
Background: The repeated act of heading has been implicated in the link between football participation and risk of neurodegenerative disease, and acutely alters cerebrovascular outcomes in men. This study assessed whether exposure to a realistic number of headers acutely influences indices of cerebral blood flow regulation in female footballers. Methods: Nineteen female players completed a heading trial and seated control trial on two separate days. The heading trial involved six headers in one hour (one every 10 minutes), with the ball travelling at 40 ± 5 km/h. Cerebrovascular reactivity to hypercapnia and hypocapnia was determined using serial breath holding and hyperventilation attempts. Dynamic cerebral autoregulation (dCA) was assessed by scrutinizing the relationship between cerebral blood flow and mean arterial blood pressure during 5 minutes of squat stand maneuvers at 0.05 Hz. Neurovascular coupling (NVC) was quantified as the posterior cerebral artery blood velocity response to a visual search task. These outcomes were assessed before and one hour after the heading or control trial. Results: No significant time by trial interaction was present for the hypercapnic (P=0.48, ηp2=0.05) and hypocapnic (P=0.47, ηp2=0.06) challenge. Similarly, no significant interaction effect was present for any metric of dCA (P>0.12, ηp2<0.16 for all) or NVC (P>0.14, ηp2<0.15 for all). Conclusion: The cerebral blood flow response to changes in carbon dioxide, blood pressure and a visual search task were not altered following six headers in female footballers. Further study is needed to observe whether changes are apparent after more prolonged exposure.